High quality design on a low budget : new library buildings : proceedings of the Satellite Conference of the IFLA Library Buildings and Equipment Section "Making ends meet: high quality design on a low budget" held at Li Ka Shing Library, Singapore Management University, 15-16 August 2013 - Sommer, Dorothea (Library administrator); Schmidt, Janine; Clevström, Stefan (IFLA publications ;, 2016)
This publication brings together a range of building projects from National, Academic and Public Libraries from different countries of the world showing how these libraries are able to continue to provide high quality library space that is affordable in times of difficult economic circumstances. We will hear about the building processes, co-operation with architects and engineers and how librarians and users have reacted to these new buildings.